PENERAPAN ETIKA PROFESI DALAM PENGAMBILAN KEPUTUSAN ETIS AUDITOR - Rasita, Elya; Putra, Bayu Trian Sandi; Virni Sagita (Journal of Management and Innovation Entrepreneurship (JMIE), 2025)
Professional ethics are moral principles and standards that regulate the behavior and actions of professionals in carrying out their duties and responsibilities. In this article, ethics is very necessary for choosing ethical decision making because the accounting profession also has a very crucial and in-depth understanding of how ethics in ethical decision making is for an auditor. The aim of this research is to clarify the relationship between professional ethics and auditor ethical decision making.  iThis research uses the iSLR method (System iLiterature iReview) and this research can help in balancing the level of significant relationships between professional ethics when making decisions, i.e. auditors and anticipating actions that are inconsistent with business etiquette and when making decisions. idecision. This research was carried out on a sample of 30 articles. The variables used in this research are professional ethics and auditor ethical decisions. iThe research results show that the application of professional ethics has a significant positive influence on auditors' ethical decisions. iThis research was participated in by three students of the iFaculty of iEconomics and iAccounting of iMuhammadiyah University iBekulu. The results of this research show that professional ethics variables independently and simultaneously have a positive and significant influence on auditors' ethical decision making. Keywords: iProfessional iethics, iEthical idecisions, iAuditor